A dynamic mathematical model for once-through boiler-turbine units with superheated steam temperature. (April 2020) - Fan, He; Su, Zhi-gang; Wang, Pei-hong; Lee, Kwang Y.
Highlights: Influence of spray water is considered in modeling coordinated control system. Effect of total feedwater flow is analyzed in modeling temperature system. Correction factors of heat function are modeled to improve model accuracy. Model structure shows the varying inertia and nonlinearity of temperature system. The model is validated by both systems of a 1000 MW once-through boiler unit. Abstract: To absorb more renewable energy generation into power grid, once-through boiler-turbine (OTBT) units are now required to operate in a wide load range while maintaining high safety and efficiency. Superheated steam temperature (SST), adjusted by spray water and feedwater together, plays a critical role on operational safety and economy. However, the models of OTBT units in existing literature have not reflected this essential interrelationship, which may deteriorate the control performances of coordinated control system (CCS) and SST system. To this end, this study proposes to develop such a dynamic mathematical model of OTBT units. Model structure is derived from mass and energy conservation laws, and static parameters and functions are identified based on running data by using nonlinear regression analysis and optimization algorithm. Dynamic validation and open-loop simulation illustrate that the model has satisfactory accuracy, reflecting essential characteristics, and thus it can be used for simulation analysis and controller design.